1992
DOI: 10.1007/bf00174196
|View full text |Cite
|
Sign up to set email alerts
|

Lipid formation in the oleaginous mould Entomophthora exitalis grown in continuous culture: effects of growth rate, temperature and dissolved oxygen tension on polyunsaturated fatty acids

Abstract: The oleaginous fungus Entomophthora exitalis was grown in continuous culture at a constant dilution rate (0.04 h -1) and over a range of temperatures (20-30 ° C). As the growth temperature was decreased from 30 to 20°C the percentage of polyunsaturated fatty acids (PUFA) increased proportionally from 18 to 27% (w/w) of the total fatty acids. The increase in unsaturation was as a result of an increased proportion of n-6 PUFA (particularly arachidonic acid) in the phospholipid and sphingo-plus glycolipid fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 14 publications
2
32
0
4
Order By: Relevance
“…The temperature can influence the lipid profile of the oleaginous mould (Kendrick and Ratledge, 1992). With the decrease of the culture temperature, the degree of saturation of fatty acid was generally decreased, the culture temperature influenced the fatty acid composition of Y. lipolytica.…”
Section: Effect Of Different Nitrogen Source On Cell Growth and Lipidmentioning
confidence: 99%
“…The temperature can influence the lipid profile of the oleaginous mould (Kendrick and Ratledge, 1992). With the decrease of the culture temperature, the degree of saturation of fatty acid was generally decreased, the culture temperature influenced the fatty acid composition of Y. lipolytica.…”
Section: Effect Of Different Nitrogen Source On Cell Growth and Lipidmentioning
confidence: 99%
“…The data presented in this paper show the significant influence which incubation temperature and supply glucose exerts on the GLA production by Mucor sp LB-54. Presumably, it is not the temperature, as such, that affects the unsaturated fatty acids but the solubility of O 2 , which increases at decreasing temperatures (13). These results suggest that Mucor sp LB-54 may have potential for commercial development for the production of GLA by fermentation techniques.…”
mentioning
confidence: 91%
“…Mortierella ramanniana (9), Mucor sp (21), Cunninghamella japonica (7), and Entomophthora exitalis (13) were reported as perspective GLA producers. Currently, only Japan is producing GLA commercially, using the fungus Mortierella (17).…”
Section: Introductionmentioning
confidence: 99%
“…GLA is also obtained from the microorganisms like Mucor spp, Mortierella spp, Cunninghamella spp. Rhizopus, Entomophthora spp, Thamnidium and Absidia [5][6][7]. These microorganisms are promising lipid sources because of their extremely high growth rates on cheap substrates and simplicity of manipulation of cellular lipid contents by environmental and nutritional conditions over the plant sources.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, temperature is one of the most critical factors that affect all species of living organisms and controlling the growth rate, lipid synthesis and alters the composition of fatty acids in cellular level. Earlier studies showed that temperature has pronounced effect on growth and biosynthesis of unsaturated fatty acids in certain oleaginous microorganisms [7][8][9][10]. Fermentation at high temperature produce more saturated than unsaturated fatty acid and vice versa when grown at low temperature.…”
Section: Introductionmentioning
confidence: 99%